Performance analysis on automated and average channel quality information (CQI) reporting algorithm in LTE-A - Mohd. Ramli, Huda Adibah; Ahamad Sukor, Masturah (IEEE, 2016)
Robust service can be achieved in error prone Long Term Evolution-Advanced (LTE-A) by dealing with imperfect Channel Quality Information (CQI). CQI is very crucial in evolved Node B (eNodeB) to decide the corresponding modulation and coding scheme in LTE and LTE-A. User Equipment (UE) will measure and estimate the CQI in order to maximize the throughput performance. Adaptive Modulation and Coding (AMC) is used in order to adapt with the channel variation environments but the wireless channel itself is subject to various impairments including imperfect CQI report which may lead to degradation of the Quality of Service (QoS). The performance of two CQI reporting algorithms which are Automated CQI Reporting Algorithm and Average CQI Reporting Algorithm are being analyzed in this paper. The simulation results demonstrated that the Average CQI Reporting Algorithm produced more promising results with the increment about 15% of the system capacity and capable to support delay up to 63.6% compared to Automated CQI Reporting Algorithm with respect to the Packet Loss Ratio (PLR)